ALGEBROIDS AND COMBINATORIAL INTERPRETATIONS - Zatorskyi, R.A.; Makhnei, O.V.; Pylypiv, V.M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
The construction of a combinatorial-algebraic structure is considered. This structure is a set of algebraic expressions. The operands of these expressions belong to some multiset M and commutative operations with a given priority belong to some set O.